1984
DOI: 10.1002/jsfa.2740351112
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Thearubigin Pigments in Black Tea Manufacturing Systems

Abstract: The formation of thearubigin pigments in prevalent commercial manufacturing systems such as orthodox roll, roll followed by curling, tearing, crushing (CTC), rotorvane combined with CTC and CTC alone was studied in the six Tocklai released clones TV-1, TV-2, TV-8, TV-9, TV-17 and TV-18. The contribution of the pigment composition, especially thearubigins of high, intermediate and low molecular weights as separated by a Sephadex LH 20 column, was examined on the basis of the types of leaves, degree of wither an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…The ®ndings shown in Fig 3 are concordant with the observations of Hazarika et al, 20 who observed that when exposed to 100°C alone, ie in the absence of thea¯avins or epicatechin, lower-mass thearubigins give rise to higher-mass thearubigins. Hazarika et al 20 showed evidence that elevated drying temperature could both retard the development of thearubigins similar to those generated by over-fermentation, and promote the transformation of lower-mass thearubigins to higher-mass thearugibins by thermal change without the presence of¯avan-3-ols or thea¯avins.…”
Section: Non-fluidized Thin Layer Dryingsupporting
confidence: 93%
See 2 more Smart Citations
“…The ®ndings shown in Fig 3 are concordant with the observations of Hazarika et al, 20 who observed that when exposed to 100°C alone, ie in the absence of thea¯avins or epicatechin, lower-mass thearubigins give rise to higher-mass thearubigins. Hazarika et al 20 showed evidence that elevated drying temperature could both retard the development of thearubigins similar to those generated by over-fermentation, and promote the transformation of lower-mass thearubigins to higher-mass thearugibins by thermal change without the presence of¯avan-3-ols or thea¯avins.…”
Section: Non-fluidized Thin Layer Dryingsupporting
confidence: 93%
“…10 The shape of this hump was not affected by the various drying treatments in the¯uidized experiment, but elevated temperature did increase the magnitude, again indicating thermal polymerisation as demonstrated by Hazarika et al 20 With short drying times as used in the¯uidized drying experiments, variations in drying had no effect on the chemical markers of fermentation and tea quality, such as the¯avan-3-ols. Other work using the same quantitative analytical methods on fermentation rather than drying has shown that these methods of assessment are sensitive to changes in tea, 15 and that the changes in drying are very much smaller than those in fermentation.…”
Section: Batch Fluidized Bed Dryingmentioning
confidence: 62%
See 1 more Smart Citation
“…Green tea infusion and some components in tea infusion (e.g., tannic acid, catechin, and caffeine) had no effects. For the manufacture of black tea, the fermentation process causes green tea polyphenols to oxidize and form oligomeric flavalols, including theaflavins, thearubigins and other oligomers (Hazarika et al, 1984;Roberts, 1958). Theaflavins and thearubigins are contained in the infusion of black tea (fermented tea) and oolong tea (semifermented tea), although the content in the infusion of oolong tea is lower than that of black tea (Xie et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Catechins account for 6-16% (Zhu & Chen, 1999) up to 30-40% (Phithayanukul et al, 2010 of the dry green tea leaves. The fermentation or semifermentation stage (when the withered leaves are rolled and crushed) during the manufacture of black or oolong tea, respectively, converts catechins to theaflavins (theaflavin, theaflavin-3-gallate, theaflavin-3'-gallate and theaflavin-3,3'-digallate, accounting for 3-6% of solid extract) and thearubigins (accounting for 12-18% of solid extract) (Leung et al, 2001;Khan & Mukhtar, 2007), which are complex polyphenols of poorly-defined chemical structures formed during fermentation of polymerization of theaflavins (Hazarika et al, 1984 …”
mentioning
confidence: 99%